2012
DOI: 10.1128/aac.00514-12
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Triazole Treatment History and Susceptibility in Clinically Isolated Aspergillus fumigatus

Abstract: b This is the first report of a detailed relationship between triazole treatment history and triazole MICs for 154 Aspergillus fumigatus clinical isolates. The duration of itraconazole dosage increased as the itraconazole MIC increased, and a positive correlation was observed (r ‫؍‬ 0.5700, P < 0.0001). The number of itraconazole-naïve isolates dramatically decreased as the itraconazole MIC increased, particularly for MICs exceeding 2 g/ml (0.5 g/ml versus 2 g/ml, P ‫؍‬ 0.03). We also examined the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 33 publications
4
72
0
Order By: Relevance
“…This isolate subsequently showed a high ITCZ MIC, revealing its resistance to ITCZ. This is likely to have been caused by the 16-month exposure to azole treatment inside the host, which is consistent with previous reports that showed that resistance mutations were generated during azole treatment (3,5,6).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This isolate subsequently showed a high ITCZ MIC, revealing its resistance to ITCZ. This is likely to have been caused by the 16-month exposure to azole treatment inside the host, which is consistent with previous reports that showed that resistance mutations were generated during azole treatment (3,5,6).…”
Section: Discussionsupporting
confidence: 80%
“…In some cases in which the strains are serially isolated from a single patient undergoing azole treatment, the first cultured isolates show azole sensitivity and carry no cyp51A mutations, whereas subsequent isolates are azole resistant and possess cyp51A mutations (3,5,6,13). Although it is not clear whether the host environment itself promotes genetic mutations, azole treatment appears to be a selective factor for cyp51A mutants.…”
mentioning
confidence: 99%
See 3 more Smart Citations